# Showing the sequence converges to the square root

For any $a > 0$, I have to show the sequence $x_{n+1}$ $=$ $\frac 12$($x_n+$ $\frac {a} {x_n}$)

converges to the square root of $a$ for any $x_1>0$.

If I assume the limit exists ( denoted by $x$) then,

$x$ $=$ $\frac 12$($x+$ $\frac {a} {x}$) can be solved to $x^2 = a$

How could I show that it does exist?

• Try to show that the sequence is monotonic and bounded, then you can conclude that the limit exists. – Mustafa Said Mar 21 '14 at 20:36
• It seemed that whether or not it increased/decreased depended on the value of $x_n$ compared to $a$ and to 1. I assumed this would mean I would have to break it into multiple cases. Is there something I missed? – user110503 Mar 21 '14 at 20:41
• we have that $x_n \geq a$ by the arithmetic-geometric mean inequality for $n \geq 2$ so you may assume that $x_n > a$. – Mustafa Said Mar 21 '14 at 20:55
• Possible duplicate of Proof of Convergence: Babylonian Method $x_{n+1}=\frac{1}{2}(x_n + \frac{a}{x_n})$ – Arnaud D. Apr 18 at 12:14

As mentioned in the comments, we need to show that the sequence is monotonic and bounded.

First, we observe that $$x_n-x_{n+1}=x_n-\frac12\Bigl(x_n+\frac a{x_n}\Bigr)=\frac1{2x_n}(x_n^2-a).$$ Secondly, we obtain that \begin{align*} x_n^2-a &=\frac14\Bigl(x_{n-1}+\frac a{x_{n-1}}\Bigr)^2-a\\ &=\frac{x_{n-1}^2}4-\frac a2+\frac{a^2}{4x_{n-1}^2}\\ &=\frac14\Bigl(x_{n-1}^2-2a+\frac{a^2}{x_{n-1}^2}\Bigr)\\ &=\frac{1}{4}\Bigl(x_{n-1}-\frac a{x_{n-1}}\Bigr)^2\\ &\ge0. \end{align*} Hence, $x_n\ge x_{n+1}$ and $x_n$ is bounded from below since $x_n^2\ge a$ for each $n\ge2$.

Monotonic and bounded sequence converges. Denote the limit of the sequence $x=\lim_{n\to\infty}x_n$. Then we have that $$x=\frac12\Bigl(x+\frac ax\Bigr)\quad\iff\quad x=\sqrt a.$$

• This argument shows that a limit exists, but how does is show that the limit is $\sqrt{a}$? – Fly by Night Mar 21 '14 at 23:22
• @FlybyNight The OP stated that he/she already knows that the limit is $\sqrt a$ if it exists. – Tunococ Mar 22 '14 at 0:08
• @FlybyNight I added the fact that the limit is $\sqrt a$ to my answer. – Cm7F7Bb Mar 22 '14 at 7:22

That looks a lot like the well known method for computing square roots. It is derived by using Newton's on

$$x^2 - a = 0$$

$$x_{n+1}=x_n-\frac{f(x_n)}{f'(x_n)}$$

$$=x_n-\frac{x_n^2-a}{2x_n}$$

$$=\frac{1}{2}\left(x_n+\frac{a}{x_n}\right)$$

If it converges it will converge to the $$\sqrt{a}$$